Rumah Perkalian Diminati Siswa SDN Aisyah Surabaya Sebagai Media Pembelajaran Matematika - Firli Febrianti; Riza Umami; Nensy Megawati Simanjuntak (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
From this research, the researcher wants to further develop learning media that uses game media so that it attracts more interest from students at SD Aisyah Surabaya. This research method is qualitative research with a descriptive approach. Data source sampling was carried out purposively in grades 4, 5 and 6. This research aims to (1) describe the use of Multiplication House media at Aisyah Elementary School in Surabaya, (2) describe how interested grade 4, 5 and 6 students are in Rumah Multiplication media. Multiplication, (3) describes the obstacles to using Multiplication House media, (4) describes solutions to overcome obstacles experienced by students. The results of the research show the following: (1) the use of the Multiplication House media can attract students' interest in learning mathematics, especially multiplication and provide assistance to students in memorizing multiplication in a fun way, (2) The obstacle to using the Multiplication House media is that students have not yet mastered multiplication. and the use of pawns made of pine so it is less safe, and (3) The solution to the problem of using Multiplication House media is that the role of teachers and parents is needed in guiding students to memorize multiplication and replace pawns with safer media. The conclusion that can be drawn is that the multiplication house media can motivate students to memorize multiplication.